Obstructive Urethrolithiasis in a Mule - Campebell, Rita de Cássia; Silva, Fernanda Barbosa da; Silva, Jorge Filipe Brito; Rehbein, Letiana da Silva; Argenta, Verônica Lourença de Souza; Ribeiro, Elissa; Braga, Gustavo Peixoto; Garcia, Laís Velloso; Câmara, Antonio Carlos Lopes (Acta Scientiae Veterinariae, 2021)
Background: Obstructive urolithiasis is a rare but potentially serious condition in equids. In the reviewed literature, there are several case reports of urolithiasis in horses and donkeys, but the only mention of this condition in mules occurred as incidental findings at a slaughterhouse. Therefore, this work aims to describe the first report and successful treatment of obstructive urethrolithiasis in a mule (Equus asinus x Equus caballus). Case: A 10-year-old castrated male mule weighing 380 kg was referred for hospital care. Tachycardia (64 beats per min), mild dehydration (7%), increased capillary filling time (3 s), slightly congested mucous membranes, and dysuria were observed. During its attempts to urinate, the mule was able to expose the penis, resulting in only dribbling of urine with reddish coloration. Urethral catheterization failed to reach the urinary bladder and revealed an obstruction at the ischial arch (7 x 4 cm), as confirmed by palpation and ultrasonography. Additionally, rectal ultrasound examination showed urine sedimentation and a single 2.36 mm vesical calculus. After sedation, local anesthesia, and surgical preparation, urethrotomy in the standing position was performed over the urethral obstruction at the ischial arch, reaching the urethrolith that fragmented during removal. Urethral catheterization from the urethrotomy site to flush the urinary bladder and urethra were performed, but the remaining vesical calculus was not retrieved. Considering the presence of a vesical calculus, severe urethral damage caused by the spiculated calculus and catheterization attempts, permanent perineal urethrostomy was performed. Laboratory tests revealed unremarkable hematological parameters, while serum biochemistry showed increased creatinine level. Urinalysis revealed cloudiness, amber appearance, countless red blood cells and bacteria, and calcium carbonate crystals. The urethrolith composition included ammonia, carbonate, and oxalate. Twelve months after surgery, the mule was healthy, the urethrostomy was viable, and no complications were recorded during this period. Discussion: Although uncommon, there are reports describing calculi of different sizes and weighing up to 803 g, causing mild to severe clinical signs according to the degree of obstruction in horses and donkeys. In the mule described here, the urethrolith did not completely obstruct the urethra, but the spiculated calculus caused dysuria and hematuria. In fact, most animals are usually referred for acute abdominal signs or hematuria and pollakiuria, but other unusual signs, such as rectal prolapse, may also be present. In the present report, the diagnosis of obstructive urethrolithiasis was established based on clinical signs and transcutaneous ultrasound of the subischial area, allowing visualization of the urethrolith. To the best of our knowledge, this is the first report of obstructive urethrolithiasis affecting a mule in Brazil. We reiterate that this condition must be included in the differential diagnosis of mules and hinnies with hematuria and dysuria, especially when associated with abdominal pain. Additionally, urethrostomy associated with urethrotomy performed on this mule in the standing position was a low-cost procedure with good results. Due to the lack of specificity regarding the food management of the mule on the previous farm, an assessment cannot be made regarding the effects of its food on urolith composition.